The decay and withering away of ECOWAS's role in West African Regional security - Saley Idrissa Ibrahim,; Zarina Othman,; Nor Azizan Idris, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
With the end of the Cold War, many countries accelerated their move towards regionalism. Although this was a common phenomenon for many Western countries such as those in the European Union (EU) and the North American Free Trade Agreement (NAFTA), it was considered new for developing regions like those in Southeast Asia and West Africa. Comparatively, in Asia, regional institutions like the Association of Southeast Asian Nations (ASEAN) has existed for almost five decades since 1967. ASEAN’s role in managing regional conflicts has been partly praised by many, although its ‘non-interference’ principle remains debatable. Unlike ASEAN, the Economic Community of West African States (ECOWAS) has been heavily criticized for its failure to make West Africa a more prosperous and stable region. It has in fact decayed in its efficiency and has become more dependent in the area of collective regional security management in the 21st Century. This trend has already started for a few years before the end of the last millennium. Currently, ECOWAS has clearly lost its vitality compared to its active security record of the early 1990s. Neo-realism was adopted in this study to explain the current West African situation. The findings highlighted the contributing factors that served as strong determinants of ECOWAS continued decline, and that gave way to extra-regional forces finding ready loopholes to encroach upon its regional sovereignty and weaken its independent initiatives. The article provides some innovative suggestions to help improve the institution in the long-run with the aim of contributing to a more prosperous and stable West Africa